2003
DOI: 10.1039/b300862m
|View full text |Cite
|
Sign up to set email alerts
|

Trace humic and fulvic acid determination in natural water by cloud point extraction/preconcentration using non-ionic and cationic surfactants with FI-UV detection

Abstract: A preconcentration and determination method for humic and fulvic acids at trace levels in natural water samples was developed. Cloud point extraction was successfully employed for the preconcentration of humic acid (HA) and fulvic acid (FA) prior to the determination by using a flow injection (FI) system coupled to a spectrophotometric UV-Vis detector. The quantitative extraction of HA and FA within the pH range 1-12 was obtained by neutralization of the anionic charge on the humic substances with a cationic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Cadmium was preconcentrated in the presence of 1.0 mg L −1 humic acid, which has been considered a normal concentration of humic substances in natural water samples. 45 The variation percentage was found to be −15%, thus indicating low influence of humic acid on the Cd 2+ preconcentration. This result corroborates the feasibility of Cd 2+ determination in lake water samples free of interference using an external analytical curve.…”
Section: 27mentioning
confidence: 93%
“…Cadmium was preconcentrated in the presence of 1.0 mg L −1 humic acid, which has been considered a normal concentration of humic substances in natural water samples. 45 The variation percentage was found to be −15%, thus indicating low influence of humic acid on the Cd 2+ preconcentration. This result corroborates the feasibility of Cd 2+ determination in lake water samples free of interference using an external analytical curve.…”
Section: 27mentioning
confidence: 93%
“…This can affect drinking water quality. HA can react with chlorine during drinking water treatment and produce disinfection byproducts (DBPs), such as trihalomethanes (THMs) and haloacetic acids (HAAs), which can cause potential health impacts [1], [2]. Hepplewhite et al reported that HA is present in drinking water at concentration levels of between 2 and 15 mg/l [3].…”
Section: Introductionmentioning
confidence: 99%
“…28 The use of cationic surfactants in combination with a non-ionic surfactant has been documented with an increase in the extraction efficiency of polar organic compounds. 29,30 Mixed-MME was used in the preconcentration of organic compounds 31 and metal cations. 32,33 Chrome Azurol S (CAS) and Alberon, a dye in the triphenylmethane series, have carboxylate groups, besides hydroxyl and sulfonate groups (Scheme 1) that react with beryllium to form the anionic complex Be(CAS)2.…”
Section: Introductionmentioning
confidence: 99%